Lessons from Implementation of Educational Reforms in Pakistan : Implications for Policy and Practice - Edited by Takbir Ali and Sarfaroz Niyozov (Karachi Oxford University Press, 2017)
A resourceful insight for stakeholders and reformers on the future of education in Pakistan, Lessons from Implementation of Educational Reforms in Pakistan: Implications for Policy and Practice offers challenging research-grounded accounts from a selection of distinct research studies, carried out by AKU-IED faculty.
Include Index
Keywords: Education -- Education and state -- Educational change